The new psychoactive substances 25H-NBOMe and 25H-NBOH induce abnormal development in the zebrafish embryo and interact in the DNA major groove - Wellington Alves de Barros (Elsevier, 2021)
Toxicological effects of 25H-NBOMe and 25H-NBOH recreational drugs on zebrafish embryos and larvae at the end of 96 h exposure period were demonstrated. 25H-NBOH and 25H-NBOMe caused high embryo mortality at 80 and 100 µg mL−1, respectively. According to the decrease in the concentration tested, lethality decreased while non-lethal effects were predominant up to 10 and 50 µg mL−1 of 25H-NBOH and 25H-NBOMe, respectively, including spine malformation, egg hatching delay, body malformation, otolith malformation, pericardial edema, and blood clotting. We can disclose that these drugs have an affinity for DNA in vitro using biophysical spectroscopic assays and molecular modeling methods. The experiments demonstrated that 25H-NBOH and 25H-NBOMe bind to the unclassical major groove of ctDNA with a binding constant of 27.00 × 104 M−1 and 5.27 × 104 M−1, respectively. Furthermore, these interactions lead to conformational changes in the DNA structure. Therefore, the results observed in the zebrafish embryos and DNA may be correlated.